THE APPLICATION OF PICTURE AND PICTURE MODELS FOR UPGRADE THE RESULT OF STUDENT LEARNING ON ENGLISH LANGUAGE BY USING SIMPLE PRESENT TENSES IN THE X CLASS OF SMA NEGERI 3 KUTACANE - Sintia Utami; Raja Fauziah; Abdul Halim (Tuwah Pande: Jurnal Ilmu Pendidikan dan Pengajaran, 2022)
Destination study this for knowing the effect of picture and picture models on results study student in using tenses for the topic of daily activity material. The method of the research is quantitative with one group pretest-posttest design. The population taken from whole class X amounted to 101, while the sample used in one class is class X IPS 1 amounted to 28 students. Data collection techniques include tests, observation, and documentation. The data analysis technique uses formula percentage to evaluate observation of the picture and picture learning model, while the test uses two formulas in between average formula and n-gain. Finding the research is pretest get the average score is 23.43, posttest get the mean score was 71.7. From the score, the that occurs enhancement understanding of the simple present tenses in the context of daily activities material. Whereas n-gain gets a score of 0.63 means that the score n-gain of 0.3 < 0.63 >0.7 is categorized as a medium, it means the level of success of the application of the picture and picture learning modelon simple present tense material is categorized as medium. Results of learning model observation picture and picture get score percentage sheet teacher observation is 82.3%, while score percentage sheet student observation is 80.2%. This thing shows that for the category sheet teacher's observation is good, while on the sheet student observation is categorized as very good, which means the teacher has succeeded apply the learning model with good.